Roadblocks to university education for diploma engineers in Bangladesh - Alam, Gazi Mahabubul; Forhad, Abdur Rahman (Emerald Publishing, 2021)
Purpose: Diploma Engineers (DE) mainly receive practical and skills-oriented education and training in the area of technical and vocational subjects from the polytechnic system. Globally, universities have limited DEs access to Higher Education (HE). Over the course of time, many countries have changed this situation, putting into place a decent qualification and policy framework that ensures higher education for deserving candidates. Lately, Technical and Vocational Education and Training (TVET) received special priority in developing countries, and Bangladesh is no exception to it, resulting in a massive growth of DE. This study, the first of its kind, examines the impact of this growth with a key focus on the inclusion of diploma engineers into higher education. Design/methodology/approach: Given the differentiated nature of research questions, multiple techniques are used to collect the data. However, this research uses the qualitative method. Both secondary and primary data are used. While secondary data are collected by the Bangladesh Bureau of Educational Information and Statistics (BANBEIS), primary data are collected through interviews. With standard sets of admission questions, tests are conducted with two groups of students to draw a comparison. Findings: The number of students studying at polytechnic institutes is increasing dramatically. The growth of public polytechnic institutes remains steady. Public counterparts respond to the demand by operating both day and night shifts. Many private polytechnics are also established. The size and infrastructure of private Polytechnics are relatively insignificant. However, the mushrooming private sector covers the increased demand. The curve of DE has been increased radically with a questionable competency by the contribution of both public and private polytechnics. Only one public university provides higher education to these DE. Originality/value: A few reports have been published in the area of TVET by the development partners and the Government of Bangladesh. Only one journal article is published exploring the role of TVET on national development in Bangladesh. However, none cover the issue of access to university education for DE graduates.